1999
DOI: 10.1095/biolreprod61.2.393
|View full text |Cite
|
Sign up to set email alerts
|

Role of Radical Oxygen Species in Rat Testicular Germ Cell Apoptosis Induced by Heat Stress

Abstract: The present study was designed to clarify the role of radical oxygen species in testicular germ cell apoptosis induced by heat stress. Testicular cells isolated from immature rats were cultured with or without elevated temperature, and occurrence of apoptosis in these cells was defined by the appearance of DNA fragmentation following agarose gel electrophoresis and by flow cytometric quantification of apoptotic cells. At 32.5 degrees C, < 1% of cells showed signs of apoptosis throughout the culture period, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
118
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(134 citation statements)
references
References 44 publications
13
118
0
2
Order By: Relevance
“…Number of interstitial cells of Leydig were found to be reduced which is shown in Figure 3. Similar was reported by Ikeda M. et al [22]. As observed in the histological section, use of Vitamin E against heat stress (group IV) showed somewhat protective effect but was not much effective.…”
Section: 64±021supporting
confidence: 88%
“…Number of interstitial cells of Leydig were found to be reduced which is shown in Figure 3. Similar was reported by Ikeda M. et al [22]. As observed in the histological section, use of Vitamin E against heat stress (group IV) showed somewhat protective effect but was not much effective.…”
Section: 64±021supporting
confidence: 88%
“…It has been shown that raised temperature can lead to oxidative stress within the rat testis; this in turn can trigger apoptosis (Ikeda et al 1999). The effects of oxidative stress on the genomic integrity of spermatozoa have been studied by inducing oxidative stress in the testis and in mature spermatozoa (Aitken et al 1989, Lucesoli & Fraga 1995.…”
Section: Discussionmentioning
confidence: 99%
“…Heat shock is also known to induce radical oxygen species, including superoxide anion (O 2 . Å ) and hydrogen peroxide (H 2 O 2 ) (Ikeda et al, 1999), and these radicals may provide an alternative pathway to ATM activation.…”
Section: Discussionmentioning
confidence: 99%